HUANIAO GENRE AND BAROQUE BOUQUETS: METAMORPHOSES OF BEING - Лай, Юеге (Art and Design, 2019)
The purpose of the study is to identify the figurative and symbolic parallels of the depiction of flowers in the art of China and Europe. Methodology. The study made use of the methods: historical-cultural, comparative, artistic-stylistic, iconological, iconographic. Results. It is shown that in the art of China and Europe, the image of flowers is interconnected with the embodiment of the ideal, beautiful. In our figurative and artistic analysis of the masterpieces of Chinese painting, it is shown that the masters of the “flowers and birds” genre, in the content and form of embodiment, follow the law of the universe formed in Taoism, according to which a cycle occurs in life, as in nature. In the genre of European floral still life of the 17th century, a philosophical, cognitive attitude of a person to the real world surrounding him is expressed. For the Dutch and Flemish still life, associated with the spiritual culture of Christianity, instructive meaning is important. Artists glorify the beauty of the world created by the Creator and, at the same time, adjusts the viewer to reflect on the transience of life. It can be seen that the formation of the European flower still life as an independent genre was influenced by the fine and decorative art of China, in particular, the “flowers and birds” (huanyao) genre. Common features with the style of gunbi (thorough paintbrush) are manifested in a careful study of colors, in a harmonious combination of realistic authenticity with the decorative and linear conventionality of the artistic image. The image of flowers in European painting and art in China is associated with the idea of harmony of the world, presented in the elements. The Baroque floral still life, like the huanyao genre, contain a deep symbolic meaning. The scientific novelty of the publication lies in the fact that for the first time it compares the huanyao genre with baroque bouquets, figurative and symbolic parallels of the image of flowers in the art of China and Europe are found. Practical significance validated the possibility of using the results of the study to develop textbooks and programs for the in-depth study of the art of China and Europe.